Validation of the City Infant Faces Database in Student and Parent Samples : Validacija Baze dojenačkih lica City na uzorku studenata i roditelja - Nakić Radoš, Sandra (Array, 2021)
The City Infant Faces Database (CIFD; Webb et al., 2018) is a database of 154 infant emotional expressions for use in experimental studies of infant facial communication, facial expression recognition, and parental sensitivity. The CIFD was validated only in a small sample from the general public and student midwives and nurses in the UK. This study, therefore, aimed to validate it in a larger sample of Croatian students and parents of 1-12 months old infants. Three-hundred and fifty students (Study 1), 422 mothers and 106 fathers (Study 2) were presented with images of Caucasian infant faces. The students rated images from the CIFD and Tromsø Infant Faces. They also completed questionnaires  measuring empathy, alexithymia, and perceiving and expressing emotions. The parents rated the valence of facial expressions of images from the CIFD. The results were consistent with the initial validation in both the students and parents" sample, except that agreement for negative images was lower for Croatian parents than in the UK study. Compared to the UK study, students rated images as more intense, clear, genuine, and reported stronger internal emotion. Furthermore, there was no difference in accuracy between mothers and fathers or between first-time parents and experienced parents. The CIFD is, therefore, a promising tool for research and should be further validated in other countries, focusing on its predictive validity.